Gift exchange in the workplace: money or attention? - Robert Dur (Center for Economic Studies and ifo Institute (CESifo), 2008)
We develop a model of manager-employee relationships where employees care more for their manager when they are more convinced that their manager cares for them. Managers can signal their altruistic feelings towards their employees in two ways: by offering a generous wage and by giving attention. Contrary to the traditional gift-exchange hypothesis, we show that altruistic managers may offer lower wages and nevertheless build up better social-exchange relationships with their employees than egoistic managers do. In such equilibria, a low wage signals to employees that the manager has something else to offer namely, a lot of attention which will induce the employee to stay at the firm and work hard. Our predictions are well in line with some recent empirical findings about gift exchange in the field.
Keywords: D86; J41; M50; M54; M55; 330; Manager-employee relationships; wages; extra-role behavior; sabotage; gift exchange; social exchange; conditional altruism; reciprocity; signaling game; Arbeitsbeziehungen; Leistungsmotivation; Soziale Beziehungen; Führungskräfte; Angestellte; Reziprozität; Altruismus; Verantwortung; Signalling; Theorie